Analisis Hukum Islam terhadap Perjanjian Perkawinan Mengenai Harta Bersama di Indonesia - Muhammad Rasyid Aqsha Hsb; Fatimah Fatimah (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2026)
This   study   aims   to   examine   prenuptial agreements concerning joint property from the perspective of Islamic Law. The research employs    a    normative    legal     approach, analyzing     commonly     used     prenuptial agreement documents. The findings reveal that   these   agreements   provide   detailed arrangements regarding the division of joint assets  and  personal  property.  Prenuptial agreements  play  a  significant  role  in  the Indonesian  marriage  legal   system,  both  in terms  of  positive   law   and   Islamic   legal principles.    Under    positive    law,     such agreements offer a strong legal foundation for regulating joint property  and  safeguarding the rights of each party involved. From the perspective   of   Islamic   law,   prenuptial agreements  align  with  the  principles   of justice  and  the  protection  of  individual ownership within a marital relationship.